Industrial Revolution 4.0 and the Future of the Agricultural Sector: A Theoretical Study on Technological Adaptation and Its Impact on Farmers’ Welfare - Hertini, Etty Sri; Risdwiyanto, Andriya (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to theoretically examine the influence of the Fourth Industrial Revolution on the future of the agricultural sector, particularly in the context of technological adaptation and its impact on farmers’ welfare. Using a literature review method and a descriptive qualitative approach, this research analyzes various scholarly sources obtained from Google Scholar and credible websites such as the World Economic Forum between 1989 and 2025. Out of 50 articles initially identified, only 26 were selected after a rigorous screening process based on relevance and credibility. The analysis results indicate that the application of digital technologies such as the Internet of Things (IoT), big data analytics, and artificial intelligence (AI) has a significant impact on improving productivity, efficiency, and farmers’ welfare. Theories such as the Diffusion of Innovation, Technology Acceptance Model, and Sustainable Livelihood Framework are used to explain the process of technology adoption and its socio-economic effects on farmers’ lives. However, the study also reveals that challenges such as low digital literacy, limited infrastructure, and unequal access to technology remain major barriers to the implementation of Industry 4.0-based agriculture in Indonesia.